Nondestructive evaluation of corrosion in varying environments using guided waves - Sharma, S.; Mukherjee, Abhijit (Taylor & Francis Inc., 2013)
This work reports nondestructive evaluation of reinforcing bars that are corroding in the presence and absence of chlorides utilizing ultrasonic guided waves. The effect of rates of corrosion and its progression in the two environments on the ultrasonic signals is discussed. Surface and core seeking guided wave modes were used to monitor beams undergoing accelerated impressed current corrosion. Effective combination of guided wave modes could relate to the differences in corrosion mechanisms and rates in the two environments. Calibration of the ultrasonic data with the physical condition of the bar in the two environments has been attempted. It is done by conducting destructive tests of mass loss, tensile strength, and pull out strength at different stages of corrosion.